The Effect of Using Cake Application on Students’ Vocabulary Mastery of Junior High School - Desi Sastria Lumban Gaol; Nur Anjelina Safna; Vilmin Artinia Zebua; Kammer Tuahman Sipayung; Ali Wafa (UIBU, 2024)
Cake application is an excellent English-learning tool for mastering English. The study aims to determine whether the Cake app affects students' vocabulary mastery. The present study used a quantitative method of experimental design. The data were collected from forty second-grade students at Junior High School (SMP) HKBP Sidorame Medan, Indonesia. The sample was divided into twenty students in the experimental group and twenty students in the control group, in which pre-and post-tests were given separately to each group and a vocabulary test was taken. The results demonstrate that the average pre-test score for the experimental group in this study was 42.8 points, while the average post-test score was 72. The average pre-test score for the control group was 42.65 points, while the average post-test score was 6.8. It was also found that Ha was accepted. However, Ho was rejected due to the fact that T-count > T-table = 4.41 > 1,686, indicating that this program is highly effective and helpful for learning English vocabulary. These findings suggest that traditional or existing methods may be less effective, highlighting the necessity for innovative approaches to vocabulary learning. Educational policymakers can use these findings to support decisions regarding the integration of successful programs into the curriculum, potentially leading to enhanced English language education standards. Furthermore, the results indicate a need for additional research to identify the specific elements of the program that most significantly impact its effectiveness. This further investigation could facilitate the refinement and optimization of the program to achieve even better outcomes.